Stereoisomer-Dependent Membrane Association and Capacity for Insulin Delivery Facilitated by Penetratin - Ditlev Birch; Edward J. Sayers; Malene V. Christensen; Arwyn T. Jones; Henrik Franzyk; Hanne M. Nielsen (MDPI AG, 2023)
Cell-penetrating peptides (CPPs), such as penetratin, are often investigated as drug delivery vectors and incorporating d-amino acids, rather than the natural l-forms, to enhance proteolytic stability could improve their delivery efficiency. The present study aimed to compare membrane association, cellular uptake, and delivery capacity for all-l and all-d enantiomers of penetratin (PEN) by using different cell models and cargos. The enantiomers displayed widely different distribution patterns in the examined cell models, and in Caco-2 cells, quenchable membrane binding was evident for d-PEN in addition to vesicular intracellular localization for both enantiomers. The uptake of insulin in Caco-2 cells was equally mediated by the two enantiomers, and while l-PEN did not increase the transepithelial permeation of any of the investigated cargo peptides, d-PEN increased the transepithelial delivery of vancomycin five-fold and approximately four-fold for insulin at an extracellular apical pH of 6.5. Overall, while d-PEN was associated with the plasma membrane to a larger extent and was superior in mediating the transepithelial delivery of hydrophilic peptide cargoes compared to l-PEN across Caco-2 epithelium, no enhanced delivery of the hydrophobic cyclosporin was observed, and intracellular insulin uptake was induced to a similar degree by the two enantiomers.